Microstructure of Platelet Aggregation and Fibrin Networks of Plasma Rich in Growth Factors by Scanning Electron Microscopy - MIYA, Yukiko; KIMURA, Kazutaka; NAKAJIMA, Masahiro; MOTOHASHI, Tomokazu; OHNISHI, Yuichi; IOKU, Yusuke; HAMADA, Yuri; KUBO, Hirohito; OKAMOTO, Tomoko; DATEOKA, Suguru (Journal of Oral Tissue Engineering, 2016)
It has been reported that plasma rich in growth factors (PRGF) is effective in clinical application, but the biological and histological details are still unknown. The purpose of this study was to examine a microstructure of PRGF by SEM. Venous blood was sampled from healthy volunteers and randomly divided the subjects into two groups, a blood clot group and a PRGF group. And the latter divided into three groups; a 0.5 mL layer placed above a buffy coat was set as Fraction 3 (F3), the 0.5 mL layer above F3 was Fraction 2 (F2), and the layer above F2 was the remaining blood serum component of Fraction 1 (F1). PRGF group hemocytes other than thrombocytes were not observed, and the surface of thrombocytes were smooth. In addition, platelet aggregation was not observed. PRGF group showed thin fibers densely arranged and a dense fibrin network and the pore size of the meshwork was smaller than platelets. This microstructure shows that PRGF is easy to entangle among the mesh of the fibrin network even without formation of platelet aggregates and it plays a role as a scaffold.